Correlational Analysis of Servant Leadership and School Climate - Black, Glenda Lee (Catholic Education: A Journal of Inquiry and Practice, 2010)
The purpose of this mixed-method research study was to determine the extent that servant leadership was correlated with perceptions of school climate to identify whether there was a relationship between principals’ and teachers’ perceived practice of servant leadership and of school climate. The study employed a mixed-method approach by first administering two validated quantitative instruments: Laub's (1998) Organizational Leadership Assessment (OLA) measured the perceived servant leadership in the schools and Hoy, Tarter, & Kottkamp’s (1991) Organizational Climate Description Questionnaire-Revised (OCDQ-RE) measured the school’s climate. These instruments were administered to a randomly selected sample of 231 full-time teachers and 15 principals working in a Catholic school board in Ontario. Upon completion of the quantitative data analysis, focus group interviews were conducted with 10% of the sample. The data revealed a significant positive correlation between servant leadership and school climate